Evaluasi Usability pada Aplikasi Mobile Pawoon Pos dengan Menggunakan Metode Usability Testing - Elsa Fajar Prakoso; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Pawoon POS is an online-based cashier application that can be accessed using mobile phones and tablets, where we can use the POS System to manage transactions in business easily. Based on data on the Google Playstore PAWOON POS received a rating of 4.0 on a scale of 5 (21/01/2021) and received reviews from approximately 1696 users. The application is felt by some users to still have problems in the usability section. The purpose of this study is to find out and calculate the usability aspects that exist in the application and identify what usability problems the respondents encountered, after knowing what problems were encountered then these problems were used as a reference for improving the interface design. The conclusions and results obtained from the usability evaluation of the PAWOON POS application based on the results from the initial evaluation to the final evaluation are, the learnability matrix for the old user category has decreased, from 1.33 to 1.18. The increase occurred in the efficiency criteria in further evaluation, all categories increased to 100%. There is also a slight increase in the memorability value where the average number of clicks from 57 clicks for respondents in the old user category becomes 58.6 in the follow-up evaluation. For the criteria for errors in further testing, the percentage of errors made by all categories of users decreased to 0%. The last criterion that has increased is satisfaction where the score obtained is 72.9.